2020
DOI: 10.1111/myc.13058
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichum keratitis: A rare yet important fungal infection of human eyes

Abstract: Summary Background Colletotrichum is a rare cause of human infection. Previous reports about Colletotrichum keratitis were limited, and most diagnoses from past reports were based on morphological distinction, which could have led to underestimation of the prevalence of Colletotrichum species. Objective We reported phylogenetic analysis, clinical feature and treatment outcome of molecularly diagnosed Colletotrichum keratitis in our hospital. Patients/Methods We recruited 65 patients with culture‐proven filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(158 reference statements)
0
12
0
Order By: Relevance
“…6 In humans, it is known to cause subcutaneous and systemic manifestations apart from keratitis and endophthalmitis. 3,[5][6][7] Cutaneous infections are in the form of hyalohyphomycosis with nodules and skin ulcers over extremities in immunocompromised patients with a history of trauma and close contact with plants. 7 It accounts for 1.85% to 3.33% of fungal keratitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 In humans, it is known to cause subcutaneous and systemic manifestations apart from keratitis and endophthalmitis. 3,[5][6][7] Cutaneous infections are in the form of hyalohyphomycosis with nodules and skin ulcers over extremities in immunocompromised patients with a history of trauma and close contact with plants. 7 It accounts for 1.85% to 3.33% of fungal keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 After isolation, differentiation of Colletotrichum from Fusarium species is based on the microbiological appearance. 3,5 Falcate conidia show similarity with Fusarium species, but differentiation is possible on the basis of its aseptate nature and the absence of conidiomata and appressoria. 8 Phylogenetic analysis of the genus Colletotrichum based on the nucleic acid sequence of the internal transcribed spacer region (ITSR) of rDNA was put forth by Cannon et al 5 It reveals that Colletotrichum genus comprises 9 major clades and a number of small clusters and isolated species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 , 42 With our limited experience, we found that there were different clinical outcomes between C. gloeosporioides SC and C. truncatum SC; the latter seemed to be more difficult to treat compared to the former. 43 Ten patients with small to medium ulcerations caused by various species infections were not treated with antifungal agents, but the infections resolved, which might be related to the patients’ immune responsiveness, a decrease in organism loading after corneal scraping/keratectomy, and the possible antifungal effects of certain antibiotics. 44 …”
Section: Discussionmentioning
confidence: 99%